The Neurospora crassa PP2A Regulatory Subunits RGB1 and B56 Are Required for Proper Growth and Development and Interact with the NDR Kinase COT1 - Shomin-Levi, Hila; Yarden, Oded (Frontiers in Microbiology, 2017)
COT1 is the founding member of the highly conserved Nuclear Dbf2-related (NDR) Ser/Thr kinase family and plays a role in the regulation of polar growth and development in Neurospora crassa and other fungi. Changes in COT1 phosphorylation state have been shown to affect hyphal elongation, branching and conidiation. The function of NDR protein kinases has been shown to be regulated by type 2A protein phosphatases (PP2As). PP2As are heterotrimers comprised of a catalytic and scaffolding protein along with an interchangeable regulatory subunit involved in determining substrate specificity. Inactivation of the N. crassa PP2A regulatory subunits rgb-1 and b56 conferred severe hyphal growth defects. Partial suppression of defects observed in the rgb-1RIP strain (but not in the Δb56 mutant) was observed in cot-1 phosphomimetic mutants, demonstrating that altering COT1 phosphorylation state can bypass, at least in part, the requirement of a functional RGB1 subunit. The functional fusion proteins RGB1::GFP and B56::GFP predominantly localized to hyphal tips and septa, respectively, indicating that their primary activity is in different cellular locations. COT1 protein forms exhibited a hyperphosphorylated gel migration pattern in an rgb-1RIP mutant background, similar to that observed when the fungus was cultured in the presence of the PP2A inhibitor cantharidin. COT1 was hypophosphorylated in a Δb56 mutant background, suggesting that this regulatory subunit may be involved in determining COT1 phosphorylation state, yet in an indirect manner. Reciprocal co-immunoprecipitation analyses, using tagged COT1, PPH1, RGB1 and B56 subunits established that these proteins physically interact. Taken together, our data determine the presence of a functional and physical link between PP2A and COT1 and show that two of the PP2A regulatory subunits interact with the kinase and determine COT1 phosphorylation state.